Mobilization of Private Finance 2018 - MDB Task Force on Mobilization (Washington, DC, 2020)
In 2015, the global community adopted the 2030 sustainable development agenda and the sustainable development goals (SDGs) that underpin it, and countries made commitments at the twenty-first conference of the parties to the United Nations (UN) framework convention on climate change. In July of the same year, the third International Conference on financing for development in Addis Ababa recognized that the financial resources needed to achieve the SDGs far exceeded current financial flows. Those mandates have created a critical role for multilateral development banks (MDBs) and other development finance institutions (DFIs) in helping attract or mobilize private investment to development projects through risk mitigation products, advisory services, and the demonstration effects of their own investments. This report contains results for private investment mobilized by financial products and investments, as well as results of direct transaction advisory services, for 2018.